A Literature Study on the Product Packaging Influences on the Customers Behavior - RAJKUMAR, AVINASH; JAIN, VIPIN (The journal of contemporary issues in business and government, 2021)
Many organizations in the business sector have focused on one tactic or another to win more profit margins for products. An effort made by the organization to get more consumers to buy their products, organizations have always been engaging in this process. Different technologies to help their products compete with the product of rivals, the packaging type is one step to make customers aware of the product. Despite the fact that perhaps the packaging as well as the manner in which the customer determines the benefit/value of the product, the packaging rationale for purchase behaviors has been thoroughly studied and the outcomes have adequately defined the connection among the packaging with the purchasing behavior of a customer. The consumer's shopping behavior depends mostly on packaging as well as its characteristics. Packaging features such as color packaging, context illustration, and packaging content, font type, wrapping design, printed details and novelty are used as indicators. As self-service grows and customers' lifestyles shift, interest in packaging as a product advertising tactic and a catalyst to impulsive purchasing behavior is rising. Package, therefore, plays a key role throughout advertising relations, particularly at the stage of sale, which may be considered to be among the key significant aspects impacting customer buying behaviors.